2005
DOI: 10.1016/j.ydbio.2005.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a conserved 125 base-pair Hb9 enhancer that specifies gene expression to spinal motor neurons

Abstract: The homeobox gene Hb9 is expressed selectively by motor neurons (MNs) in the developing CNS. Previous studies have identified a 9-kb 5' fragment of the mouse Hb9 gene that is sufficient to direct gene expression to spinal MNs in vivo. Here, we sought to identify more discrete MN-specifying elements, using homology searches between genomic sequences of evolutionarily distant species. Based on homology screening of the mouse and human Hb9 promoters, we identified a 3.6-kb Hb9 enhancer that proved sufficient to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 38 publications
4
71
0
Order By: Relevance
“…The transcription factor hb9 is found in developing motor neurons of both mammals (William et al, 2003) and zebrafish (Cheesman et al, 2004;Park et al, 2004). In the hb9-GFP transgenic fish, motor neurons are labeled with strong neuron-specific expression of GFP under the control of the regulatory elements of the zebrafish hb9 gene (Flanagan-Steet et al, 2005;Nakano et al, 2005). Post-treatment with ketamine, images of the hb9-GFP transgenic embryos were acquired using an Olympus SZX 16 binocular microscope and a DP72 camera.…”
Section: Live Embryo Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The transcription factor hb9 is found in developing motor neurons of both mammals (William et al, 2003) and zebrafish (Cheesman et al, 2004;Park et al, 2004). In the hb9-GFP transgenic fish, motor neurons are labeled with strong neuron-specific expression of GFP under the control of the regulatory elements of the zebrafish hb9 gene (Flanagan-Steet et al, 2005;Nakano et al, 2005). Post-treatment with ketamine, images of the hb9-GFP transgenic embryos were acquired using an Olympus SZX 16 binocular microscope and a DP72 camera.…”
Section: Live Embryo Imagingmentioning
confidence: 99%
“…Importantly, in another study we also showed that acetyl L-carnitine counteracts ketamine's negative effects on heart rate and ERK (MAPK) activity in zebrafish embryos (Kanungo et al, 2012). In order to quantitate the effect of ketamine on motor neurons in vivo, hb9:green fluorescent protein (hb9:GFP) transgenic zebrafish embryos were used, in which the promoter of the transcription factor hb9 that is found in developing motor neurons of both mammals (William et al, 2003) and zebrafish (Cheesman et al, 2004;Park et al, 2004), drives GFP expression specifically in motor neurons (Flanagan-Steet et al, 2005;Nakano et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, genetic studies in mouse, chicken, and frog embryos have recently suggested that Hlxb9 is expressed selectively by postmitotic MNs in the developing vertebrate spinal cord, important for the consolidation and maintenance of MN identity [Saha et al, 1997;Arber et al, 1999;Lee and Pfaff, 2003;Lee et al, 2004;Nakano et al, 2005]. We will focus on transcription factor pathways involved in MN specification to identify possible candidate genes.…”
Section: Future Prospectsmentioning
confidence: 99%
“…We will focus on transcription factor pathways involved in MN specification to identify possible candidate genes. Nonspecific general activator proteins such as E2F and Sp1 located throughout the neural tube interact with the proximal region of HLXB9-gene promoter and nonselectively stimulate HB9 transcription [Nakano et al, 2005]. High level of Hlxb9 expression in postmitotic MNs is activated and maintained by specific transcription factors binding two recently identified, nonoverlapping MN-specific enhancer-complexes, namely a 125-base pair (bp) region (from -8557 to -8412 bp upstream of the HLXB9 gene starting codon) and a 246-bp region (from -7621 to -7409 bp) [Arber et al, 1999;Lee and Pfaff, 2003;Lee et al, 2004;Nakano et al, 2005].…”
Section: Future Prospectsmentioning
confidence: 99%
See 1 more Smart Citation